(untitled) (The Lumbini Journal of Business and Economics, 2026)
Purpose: The study examines the predictors of student satisfaction and their effect on psychological well-being among students of QAA-certified community campuses in Kathmandu district. Methods: A quantitative research design was used. Primary data were collected through a structured questionnaire out of 620 distributed questionnaires, 577 valid responses were analyzed using SPSS version 26 and AMOS version 24. Reliability test, confirmatory factor analysis, and structural equation modelling were applied. Results: The study found that extracurricular activities, infrastructure, canteen facility, library facility, teaching and learning, and college management significantly influenced student satisfaction. Among these, teaching and learning had the strongest effect. Student satisfaction also showed a significant positive effect on psychological well-being and played a mediating role between institutional factors and psychological well-being. Conclusion: The study concludes that better institutional support and learning service can improve student satisfaction and promote psychological well-being. Future research can expand this study to other areas using mixed methods.